Molecular farming- importance of stewarding food crops engineered to produce transferred food allergens and non-food substances - Dietz, Jason K.; Muldoon-Jacobs, Kristi (Frontiers in Sustainable Food Systems, 2024)
Developers are looking for new ways to produce proteins and other substances for food, pharmaceutical and industrial use by genetically engineering food crops to produce the desired substance of interest (i.e., molecular farming). Developers should be aware of the food safety concerns, legality and potential liability, and loss of consumer confidence that could arise if food or other plant materials from these crops were to inadvertently enter the food supply and compromise safety. At the earliest stages of product development, developers should consider whether it is feasible to consistently steward their crops and resulting plant materials from development through disposal to ensure they do not enter the food or feed supply in a way that would be unlawful. Developers should engage FDA’s foods program when considering their stewardship program. While molecular farming holds promise for the economical production of specific proteins and other substances at a large scale, it is important for developers to consider the efforts needed to protect the food supply from the crops used for molecular farming- particularly when the crop chosen for molecular farming is a crop traditionally used for human or animal food.